Clinical Practice Guidelines for Rheumatoid Arthritis PANLAR: A Comprehensive Approach for All - Estefania Fajardo (Global Rheumatology)
"After 15 years, PANLAR will update the Rheumatoid Arthritis (RA) guidelines, aiming to address the specificities of healthcare systems and disease management in its member countries. Additionally, it hopes to make them user-friendly for diverse strategic audiences."